Perlindungan HKI Terhadap Kuliner Tradisional Melayu Tanjungpinang Dalam Perspektif Ekonomi Kreatif - Muhammad Mumtaz Maulana; Venny Fiola Angelica; Martassya Martassya; Nurul Iman; Lia Nuraini (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Tanjungpinang’s traditional Malay culinary heritage constitutes a form of traditional knowledge possessing both cultural and economic value, thereby necessitating appropriate legal protection. Due to its communally developed nature, its protection cannot rely solely on conventional Intellectual Property Rights (IPR) regimes such as copyright, trademarks, or geographical indications. This study aims to analyze the legal protection of Tanjungpinang’s traditional Malay culinary heritage from the perspective of Communal Intellectual Property (CIP) and to examine the legal rationale for why CIP serves as the most suitable form of protection for supporting the creative economy. The study employs a normative legal research method, utilizing statutory, conceptual, and comparative approaches. The findings indicate that Tanjungpinang’s traditional Malay culinary heritage meets the criteria for Traditional Knowledge classified as Communal Intellectual Property; consequently, legal protection should commence with the inventory and registration of said CIP. Such protection can subsequently be reinforced through other IPR regimes such as geographical indications or collective trademarks tailored to the specific characteristics of each product. Thus, strengthening CIP protection not only provides legal certainty regarding the Malay community's cultural heritage but also fosters the development of the creative economy by preserving culture, enhancing the competitiveness of MSMEs, and reinforcing regional identity.